2021
DOI: 10.9767/bcrec.17.1.12392.65-77
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnetic Catalyst Derived from Oil Palm Empty Fruit Bunch for Esterification of Oleic Acid: An Optimization Study

Abstract: Biomass, renewable, abundantly available and a good source of energy. The conversion of biomass waste into valuable products has received wide attention. In this study, an empty fruit bunch (oil palm EFB) supported magnetic acid catalyst for esterification reaction was successfully prepared via the one-step impregnation process. The new magnetic catalyst achieved a higher surface area of 188.87 m2/g with a total acidity of 2.4 mmol/g and identified iron oxide as g-Fe2O3. The magnetization value of 24.97 emu/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…1113 and 1030 cm -1 (Ibrahim et al, 2020). Furthermore, the successful Fe attachment by impregnation was indicated at 540 cm -1 (Krishnan et al, 2022). This result revealed that the acidity behaviour of CO-SO3H-Fe was related to the presence of -OH, -COOH and -SO3H, and the quantitative measurement is shown in Table 2.…”
Section: Catalyst Characterizationmentioning
confidence: 76%
See 4 more Smart Citations
“…1113 and 1030 cm -1 (Ibrahim et al, 2020). Furthermore, the successful Fe attachment by impregnation was indicated at 540 cm -1 (Krishnan et al, 2022). This result revealed that the acidity behaviour of CO-SO3H-Fe was related to the presence of -OH, -COOH and -SO3H, and the quantitative measurement is shown in Table 2.…”
Section: Catalyst Characterizationmentioning
confidence: 76%
“…FT-IR was used to identify the functional groups on the surface of CO and CO-SO3H-Fe particles (Figure 3a). The vibrational mode of O-H, C-H, C=O (carboxylic acid), and C=C (aromatic carbon) was detected at 3328, 2924, 1710, and 1533 cm -1 , respectively (Araujo et al, 2021;Ibrahim et al, 2019;Krishnan et al, 2022). Furthermore, the bands at 1230 and 1020 cm -1 were attributed to the stretching vibration of cellulose and pyranose ring skeletal (Krishnan et al, 2022).…”
Section: Catalyst Characterizationmentioning
confidence: 96%
See 3 more Smart Citations